Transforming Indian agriculture through conservation agriculture - Kaur, Ramanjit; Ali, Sk Asraful; Meena, Dileep; Sankati, Jhonsonraju (Indian Farming, 2026)
Conservation Agriculture (CA) offers a transformative approach to Indian agriculture, addressing problems like soil degradation, scarcity of water, and climate variability. By adhering to the core principles of negligible soil disturbance, permanent soil cover, and diversified crop rotations, CA enhances soil health, improves water-use efficiency, and builds resilience against erratic weather patterns. The adoption of practices such as zero-tillage, mulching and crop rotation has demonstrated promising results in growing crop yields, decreasing water consumption, and mitigating environmental impacts. CA’s potential to restore soil fertility, reduce dependence on chemical inputs, and promote long-term sustainability positions it as a key strategy for ensuring the future of Indian agriculture and improving the livelihoods of farmers.